Stability of \(n\)-bi-Jordan Homomorphisms on Commutative Algebras - Zivari-Kazempour, A. (Communications in Mathematics and Applications, 2018)
In this paper, we prove that every \(n\)-bi-Jordan homomorphism between commutative algebras is an \(n\)-bi-ring homomorphism, and then we employ this result to show that to each approximate \(n\)-bi-Jordan homomorphism \(φ\) between commutative Banach algebras there corresponds a unique \(n\)-bi-ring homomorphism near to \(φ\).